Ambiguities in a Problem in Planar Geodesy - Schicho, J.; Gallet, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
This is a study of a problem in geodesy with methods from complex algebraic geometry: for a fixed number of measure points and target points at unknown position in the Euclidean plane, we study the problem of determining their relative position when the viewing angles between target points seen from measure points are known. In particular, we determine all situations in which there is more than one solution.